Razveljavitev vpisa dokapitalizacije v sodni register - Šlamberger, Miha (Podjetje in delo, 2021)
The article examines the question of how the investor and corporate bodies of a stock company react in the case of the annulment of the registration of the capital increase in the courts' register after the deadline set in the subscription share certificate. In a specific case, the problem has come up whether it is actually possible to remedy the registration proposition despite the guidance given by the court of appeal, by simply supplementing the existing proposition or filing a new registration proposition with complete accompanying documents. The guidance given by the Slovene court differs from the German courts.
Keywords: capital increase; nastop razveznega pogoja; occurrence of resolving condition; povečanje osnovnega kapitala; subscription agreement; subscription share certificate; vpisna pogodba; vpisnica